A atitude em boletins de ocorrência de crimes de linguagem contra a honra : um estudo da ofensa verbal na perspectiva do sistema de avaliatividade - Ribeiro, Marcos Rogério; Fuzer, Cristiane (Language and Law / Linguagem e Direito, 2017)
This paper presents an analysis of occurrences of evaluation within the subsystem of Attitude in the Appraisal System, taken from narrative sections of police reports (PRs) about language crimes against honor. The study was based on the principles of Systemic Functional Grammar (Halliday e Hasan, 1989; Halliday e Matthiessen, 2004) and the System of Appraisal (Martin e White, 2005). The narrative sections of six Police Reports (PRs) about crimes against honor were analyzed, two concerning calumny, two defamation and two injury. These extracts were randomly chosen from a corpus of 2,343 PRs which had been filed by the Civil Police, in September, 2011, across the whole of the State of Rio Grande do Sul. The quali-quantitative analysis using the three subsystems of Attitude identified explicit negative attitudinal evaluation in all the samples, with a predominance of judgment of social sanction in the PRs concerned with calumny and judgment of social esteem and social sanction in PRs concerned with defamation and injury. In crimes of calumny and defamation, the derogatory evaluation of victims is realized in reported projected clauses, which describe the facts with the offensive content, whereas in crimes of injury, the attitudinal pejorative evaluation is not described in facts, but is realized by epithets functioning as Attributes in projected relational clauses and as Verbiage in projected verbal clauses.